CRYPTOCOCCAL MENINGITIS IN IMMUNOCOMPETENT PATIENT - Arif, Saeed; Ghazanfar, Khushbakht; Muhammad, Waseem Wali; Malik, Hamza (Journal of Ayub Medical College Abbottabad, 2015)
Cryptococcal meningitis (CM) is life threatening fungal infection of central nervous system (CNS). Although it is commonly associated with immunosuppression but rarely it can occur in immune competent patient. We report a case of 21 year old non HIV infected girl. Based on initial diagnoses of tuberculosis Bacillus meningitis (TBM), she was started on anti-tuberculosis treatment (ATT). However failure to respond to treatment prompted a quest for alternative diagnosis. A final Diagnosis of CM was confirmed on latex agglutination antigen detection on cerebrospinal fluid (CSF) analysis. The patient responded well to antifungal treatment. Initially diagnosis was missed due to common occurrence of tuberculosis infection in Pakistan and resemblance of its symptomatology and magnetic resonance imaging (MRI) findings with CNS cryptoccocal infection.